IFPRI Strategy 2013-2018 - International Food Policy Research Institute (International Food Policy Research Institute, 2013)
Strategic research areas: 1. Ensuring sustainable food production 2. Promoting healthy food systems 3. Improving markets and trade 4. Transforming agriculture 5. Building resilience 6. Strengthening institutions and governance